In-hospital symptomatic venous thromboembolism and antithrombotic prophylaxis in Internal Medicine - Gussoni, Gualberto; Campanini, Mauro; Silingardi, Mauro; Scannapieco, Gianluigi; Mazzone, Antonino; Magni, Giovanna; Valerio, Antonella; Iori, Ido; Ageno, Walter; the GEMINI Study Group; on behalf of (Thrombosis and Haemostasis, 2009)
Hospitalised medical patients are at increased risk of venous thromboembolism (VTE), but the incidence of hospitalisation-related VTE in unselected medical inpatients has not been extensively studied, and uncertainties remain about the optimal use of thromboprophylaxis in this setting. Aims of our prospective, observational study were to assess the prevalence of VTE and the incidence of symptomatic, hospitalisation-related events in a cohort of consecutive patients admitted to 27 Internal Medicine Departments, and to evaluate clinical factors associated with the use of thromboprophylaxis. Between March and September 2006, a total of 4,846 patients were included in the study. Symptomatic VTE with onset of symptoms later than 48 hours after admission (”hospital-acquired” events, primary study end-point) occurred in 26 patients (0.55٪), while the overall prevalence of VTE (including diagnosis prior to or at admission) was 3.65٪. During hospital stay antithrombotic prophylaxis was administered in 41.6٪ of patients, and in 58.7% of those for whom prophylaxis was recommended according to the 2004 Guidelines of the American College of Chest Physicians. The choice of administering thromboprophylaxis or not appeared qualitatively adherent to indications from randomised clinical trials and international guidelines, and bed rest was the strongest determinant of the use of prophylaxis. Data from our real-world study confirm that VTE is a relevant complication in patients admitted to Internal Medicine Departments, and recommended tromboprophylaxis is still under-used, in particular in some patients groups. Further efforts are needed to better define risk profile and to optimise prophylaxis in the heterogeneous setting of medical inpatients.
Keywords: Deep venous thrombosis; pulmonary embolism; prophylaxis; management of disease